Data Analytics of the Scopus 2025 Dataset: Trends in Open Access, Publisher Influence, and Subject Area Distribution - Ahmed Shaban, Awaz; Yasin, Hajar Maseeh (Polaris Global Journal of Scholarly Research and Trends, 2025)
This study performs an extensive analysis of the Scopus Sources Dataset (February 2025 edition) using big data analytics and visualization techniques. Through systematic preprocessing, exploratory data analysis, and graphical interpretation, we investigate the structure of global scientific publishing. Key insights include the distribution of journals by source type, publisher dominance in both Open Access (OA) and Non-OA domains, ISSN/EISSN patterns, and ASJC field classification frequencies. Results show strong clustering in specific publishers and fields, a moderate OA presence, and a considerable share of journals with dual ISSN registration. Our findings provide a comprehensive snapshot of the scholarly publishing landscape as captured in Scopus 2025.